More Theatre Works by Ramón Otero Pedrayo - Tato Fontaíña, Laura (Madrygal. Revista de Estudios Gallegos, 2023)
The author of this article presents for the first time a group of fifty-four texts by Ramón Otero Pedrayo which were published in the Parladoiro section of La Noche between 1946 and 1949 and which enlarge the catalogue of plays by this author. All these texts are dialogues, some complete and others in most sections of them. The article starts with a presentation that summarizes the studies carried out so far about Ramón Otero Pedrayo’s theatre works and film screenplays. In the second part of this article there is a classification into two different categories of those fifty-three recovered texts based on their dramaturgic characteristics. The third section groups those texts according to the writer’s main topics in his literature, including a summary of each of them. As an appendix there is an updated version of two of those short texts: “Teatro de máscaras” and “Ecos do Portal”, which appear as a representation of each of the two proposed categories.